Overview of data analysis and reporting tools in the context of the SIGMA project. Issue 8 (7th August 2019) - Cocca, Giampaolo; Lindberg, Ann
Abstract : The SIGMA project aims at supporting the development and implementation of technical features with the goal of reducing the burden for the MSs to submit ad hoc animal disease and population data to EFSA. This document reports the work that has been conducted as part of the objective 4 of Work Package 7 (WP7) of the Sigma σ project, focusing on the actions taken to gather detailed information on the tools for data analysis and reporting of disease outbreaks/surveillance activities, adopted or available among the EU Member States. The technical feasibility of the integration of some of the inventoried tools into EFSA's dashboard is assessed, as well as the main features which make them suitable for their implementation as interactive web‐tools designed to produce graphs, diagrams, tables or full reports to fulfil the EU legislation.